Atomic scale porous Zn-doped carbon interlayers for high-performance Pt-ionomer interfaces - Weimin Zhou; Xiao Liu; Jianhua Wu; Hang Liu; Bin Shan; Rong Chen (Chemical Engineering Journal, 2026)

In situ polymerization-prepared water-stable CsPbX3/PMMA composites for water-stimulated anti-counterfeiting and bioimaging - Rong Huang; Xiaoman Xiang; Danxia Zheng; Geyu Feng; Xinyu Ge; Rongze Zhu; Peng Chen; Xueling Chang; Xiao-Chun Hang; Xiaoyang Qi; Longfei Ruan (Chemical Engineering Journal, 2026)

Atomically dispersed Cu-doped TiO2 derived from MOF for photocatalytic hydrogen evolution - Hao Song; Hang Zhao; Xiao Yan; Xun Zhu; Rong Chen; Qiang Liao (Chemical Engineering Journal, 2026)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Machine learning for time series prediction of valley deformation induced by impoundment for high arch dams - Hang-Hang Zang; Dian-Qing Li; Xiao-Song Tang; Guan Rong (Bulletin of Engineering Geology and the Environment, 2025)

Efficient Bayesian updating for deformation prediction of high rock slopes induced by excavation with monitoring data - Dian-Qing Li; Hang-Hang Zang; Xiao-Song Tang; Guan Rong (Engineering Geology, 2024)

Damming-associated landscape change benefits a wind-dispersed pioneer plant species - Hang Ji; Yong-Rong He; Hong-Yue Li; Ling Lu; Jia-Hui Li; Jie Zou; Rong Wang; Jun-Yin Deng; Xiao-Yong Chen (New Forests, 2024)

Influence analysis of network evolution on Parrondo effect - Ye Ye; Zhuo-yuan Zhai; Xiao-Rong Hang; Neng-gang Xie (BioSystems, 2024)

Bacterial community diversity and underlying assembly patterns along vertical soil profiles in wetland and meadow habitats on the Zoige Plateau, China - Hao-Cai Wang; Jin-Feng Qi; De-Rong Xiao; Yi Wang; Wei-Yu Shi; Hang Wang (Soil Biology and Biochemistry, 2023)

Daphnia magna uptake and excretion of luminescence‐labelled polystyrene nanoparticle as visualized by high sensitivity real-time optical imaging - Yu-Hang Zhang; Rong-Yao Gao; Ze-Jun Wang; Qian-Qian Shao; Ya-Wen Hu; Hua-Bing Jia; Xiao-Jing Liu; Feng-Qin Dong; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2023)

Comparative study of encapsulated cannabidiol ternary solid dispersions prepared by different techniques: The application of a novel technique jet milling - Hang Li; Tian-Xiao Yang; Qing-Sheng Zhao; Shou-Bu Hou; Rong-Rong Tian; Bing Zhao (Food Research International, 2023)

Corrigendum to “Promotional effects of calcination temperature and H2O on the catalytic activity of Al-substituted MnAlO catalysts for low-temperature acetone oxidation” [Chemosphere 301 (2022) 134722] - Wan-Peng Zhang; Kun Wu; Junyi Zhao; Jun He; Leiping Wang; Hang Xiao; Jian-Bing Guo; Jian-Rong Li (Chemosphere, 2023)

Nitrogen doped titania stabilized Pt/C catalyst via selective atomic layer deposition for fuel cell oxygen reduction - Hang Liu; Qizi Lu; Yuxin Gao; Chaojun Huang; Aimin Zhang; Feng Liu; Henghui Xu; Xiao Liu; Bin Shan; Rong Chen (Chemical Engineering Journal, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

Research progress of the POP fugacity model: a bibliometrics-based analysis - Meng-rong Yang; Xiao-rong Dai; Zhong-wen Huang; Cen-yan Huang; Hang Xiao (Environmental Science and Pollution Research, 2022)

Wuzi Yanzong pill attenuates MPTP-induced Parkinson’s Disease via PI3K/Akt signaling pathway - Wei Hang; Hui-jie Fan; Yan-rong Li; Qi Xiao; Lu Jia; Li-juan Song; Yao Gao; Xiao-ming Jin; Bao-guo Xiao; Jie-zhong Yu; Cun-gen Ma; Zhi Chai (Metabolic Brain Disease, 2022)

Isolation of two sesquiterpene glycosides from Sapindus mukorossi Gaertn. with cytotoxic properties and analysis of their mechanism based on network pharmacology - Min-ping Wei; Xiao-wen Zhu; Hang Yu; Yun-fei Xie; Ya-hui Guo; Yu-liang Cheng; He Qian; Wei-rong Yao (Natural Product Research, 2021)

Identifying the Pollution Characteristics of Atmospheric Polycyclic Aromatic Hydrocarbons Associated with Functional Districts in Ningbo, China - Lei Tong; Cheng-Hui Peng; Zhong-Wen Huang; Jing-Jing Zhang; Xiao-Rong Dai; Hang Xiao; Neng-Bin Xu; Jun He (Bulletin of Environmental Contamination and Toxicology, 2019)

Bacterial composition and spatiotemporal variation in sediments of Jiaozhou Bay, China - Xin Liu; Hang-Wei Hu; Yu-Rong Liu; Ke-Qing Xiao; Fan-Sheng Cheng; Ji Li; Tian Xiao (Journal of Soils and Sediments, 2015)

De novo analysis of the Tenebrio molitor (Coleoptera: Tenebrionidae) transcriptome and identification of putative glutathione S-transferase genes - Su Liu; Xiao-Xiao Shi; Yan-Dong Jiang; Zi-Jie Zhu; Ping Qian; Min-Jing Zhang; Hang Yu; Qing-Zi Zhu; Zhong-Jun Gong; Zeng-Rong Zhu (Applied Entomology and Zoology, 2015)

Effects of Estradiol on Voltage-Gated Potassium Channels in Mouse Dorsal Root Ganglion Neurons - Juan Du; Qiang Wang; Fang Hu; Jun Wang; Haixia Ding; Rong Gao; Hang Xiao; Lin Wang (The Journal of Membrane Biology, 2014)

The rare intracellular RET mutation p.S891A in a Chinese Han family with familial medullary thyroid carcinoma - Xiao-Ping Qi; Rong-Xin Zhang; Jin-Lin Cao; Zhen-Guang Chen; Hang-Yang Jin; Ren-Rong Yang (Journal of Biosciences, 2014)

In vitro antifungal activity of antifungalmycin 702, a new polyene macrolide antibiotic, against the rice blast fungus Magnaporthe grisea - Zhi-Qiang Xiong; Xiao-Rong Tu; Sai-Jin Wei; Lin Huang; Xun-Hang Li; Hui Lu; Guo-Quan Tu (Biotechnology Letters, 2013)

Persistence and intergenerational transmission of differentially expressed genes in the testes of intracytoplasmic sperm injection conceived mice - Li-ya Wang; Ning Wang; Fang Le; Lei Li; Le-jun Li; Xiao-zhen Liu; Ying-ming Zheng; Hang-ying Lou; Xiang-rong Xu; Xiao-ming Zhu; Yi-min Zhu; He-feng Huang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Expression of calmodulin in germ cells is associated with fenvalerate-induced male reproductive toxicity - Xiaohua Gao; Qiang Wang; Jun Wang; Changsong Wang; Liang Lu; Rong Gao; Fei Huan; Darlene Dixon; Hang Xiao (Archives of Toxicology, 2012)

Silicon-mediated amelioration of zinc toxicity in rice (Oryza sativa L.) seedlings - Hai-Hong Gu; Shu-Shun Zhan; Shi-Zhong Wang; Ye-Tao Tang; Rufus L. Chaney; Xiao-Hang Fang; Xin-De Cai; Rong-Liang Qiu (Plant and Soil, 2012)

Synthesis and insecticidal activities of novel derivatives of podophyllotoxin - Ying-Qian Liu; Liu Yang; Yanqing Liu; Xudong Di; Hang Xiao; Xuan Tian; Rong Gao (Natural Product Research, 2007)